Hingeless Negative Linear Compression in the Mechanochromic Gold Complex [(C6F5Au)2(μ‐1, 4‐diisocyanobenzene)]1. Issue 37 (2nd August 2013) - Woodall, Christopher H.; Beavers, Christine M.; Christensen, Jeppe; Hatcher, Lauren E.; Intissar, Mourad; Parlett, Andrew; Teat, Simon J.; Reber, Christian; Raithby, Paul R.
<x xml:space="preserve">Abstract</x> Growing under pressure: High‐pressure crystallographic and Raman spectroscopic studies show that crystals of the linear digold complex [(C6F5Au)2(μ‐1, 4‐diisocyanobenzene)] undergo substantial negative linear compression over the pressure range from ambient to 4.39 GPa.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>